KARAKTERISTIK KONSUMSI ENERGI PADA KELUARGA MISKIN UNTUK IDENTIFIKASI CEPAT KELUARGA DEFISIT ENERGI - Sri Prihatini; Vita Kartika; Syafrudin Syafrudin; Abas Basuni Jahari (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2000)
CHARACTERISTIC ENERGY CONSUMPTION IN POOR FAMILY FOR RAPID IDENTIFICATION OF DEFICIT ENERGY FAMILY.Background: Many kinds of aid for poor family has distributed by the government to overcome the effect of economic crisis. But often, the aida given is not in right target, so that the selection of the receiver needs to be selectively.Objective: The objective of this study is to develop the method identification of deficit energy family through the information of staple food consumption.Method: The socioeconomic status and food consumption data, was collected from 200 household in four villages which has the highest of poor family in four sub district in the district of Karawang, West Java. From each villages randomly choose 40 poor families and 10 un poor families.Result: The result of sensitivity test and specificity between family category and energy sufficiency is 90% of poor family is in deficit energy and only 23% of un poor family is not in deficit energy (Se=90%, and Sp=23%). At poor family which is in deficit energy, more than 80% energy is from the staple food (rice) and at un poor family which is not deficit energy only about 50%. The result of try out from developed method for rapid identification of deficit energy family through the information of staple food consumption has high sensitivity and specificity (Se=80.3% and Sp=76.9%).Conclusions: The study was conclude that this method can be used as one of instrument for identifying the poor family which needs the aid.Key Worda: staple food consumption, poor family, deficit energy family